A methods engineering study on Renew Ventures, Inc. - Marzan, Rhamel; Revilloza, Rea Mae.; Zanoria, Susan Claire (Diliman, Quezon City College of Engineering, 2005)
Renew Venture's Inc. is a warehousing and delivery company that exclusively caters for San Miguel Corporation. They deliver and store beer products as well as segregate empty bottles that are to be refilled. This study was done to check and sustain the level of quality in the company's operations, identify bottleneck operations, and evaluate work environment conditions. System documentation was done as an introduction of the group to company operations. The systems and procedures, process flow, working conditions, equipment and tooling, and facility layout were all discussed. Interviews, ocular visits and time study were done to assess the major problem areas as seen by both management and workers. Problems were identified using a Streamline Diagram. From this, 4 major problems were identified and these are worker fatigue, frequent/prolonged break times by workers, defects and process delays. A time study was conducted for the segregation process since it emerged as the bottleneck operation. A standard time of 19.752 minutes/pallet was calculated. This equated to 79.097 percent efficiency. This time study may be the cause of the process delays occuring in the day-to-day operations. Recommendations were then formulated in order to answer these problem areas. The generation of these recommendations was explained by listing their advantages and disadvantages. Defects were not included since the estimate of loss due to bottle breakages and returned bottles turned out to be negligible. The proposed solutions for worker fatigue are the proper training of workers, use of protective gear, provision of drums, and the strict implementation of rules. For frequent/prolonged break times, the recommendations are conducting a formal worker evaluation, providing a proper incentive system for the workers, and setting a standard time in the segregation process. Then, lastly for process delays, the recommendation is to fix the "holes" in the premises. Implementation plans were also written in order to aid the company on how to properly enact the recommended solutions. The specific steps on how these proposals can be done, who are directly responsible for such changes, and the duration of these recommendations were enumerated.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Renew Ventures Incorporated; Warehouses -- Management; Systems analysis